El ámbito objetivo de aplicación de la Ley de Represión de la Competencia Desleal, con especial referencia a la llamada “Competencia Prohibida” - Zegarra Mulánovich, Álvaro (2017)
This paper analyses the definition that the Act on Suppression of Unfair Competition adopted by Legislative Decree 1044 makes of its own objective scope. The positive concept of “act of competition”, that is the centerpiece of such a definition, is examined first, to then focus on the concepts excluded from it, either explicitly or implicitly, in line with both national and comparative legislation and case law. Particular attention is given to the exclusions from the concept of “act of competition” grouped in the literature under the name of “forbidden competition”.